(untitled) (Research, Society and Development, 2025)
Scorpions represent a growing public health problem in the state of São Paulo, with the species Tityus serrulatus being the most prevalent. Public cemeteries are considered vulnerable areas with high scorpion collection, which sometimes disperse to adjacent properties. The objective of this study was to implement a complementary mechanism to the scorpion management carried out in cemeteries, aiming to reduce occurrences in properties in their surroundings. An inverted PVC pipe gutter was installed around the entire area of ​​the cemetery, on the inside of the wall. The pipe joints were designed to create a structure that prevented cracks. To correct small gaps between the wall and the pipe installation, it was filled with expanding foam. It has been observed that cockroaches and scorpions are unable to cross the fixed gutter and do not reach homes. Between 2018 and 2021, there were 52 scorpions occurring in the surrounding homes. After this structure was installed, there were no more reports of scorpions in the surrounding houses. The results demonstrated a direct impact, preventing scorpions from escaping from the cemetery and entering neighboring houses, thereby positively impacting the safety of the population. This finding can be incorporated into public policies and the control of infestations of this arachnid, with significant implications for human health.